Characteristics and risk factors of relapses in patients with adult-onset Still's disease: a long-term cohort study. (26th January 2021) - Meng, Jianfen; Chi, Huihui; Wang, Zhihong; Zhang, Hao; Sun, Yue; Teng, Jialin; Hu, Qiongyi; Liu, Honglei; Cheng, Xiaobing; Ye, Junna; Shi, Hui; Wu, Xinyao; et al.
Abstract: Objectives: To describe the detailed characteristics and explore the potential risk factors of relapses in patients with adult-onset Still's disease (AOSD). Methods: We enrolled patients with AOSD admitted to the Department of Rheumatology and Immunology, Ruijin Hospital from August 2016 to September 2019. Kaplan–Meier curves and the log rank test were used to estimate the cumulative relapse probability and persistent remission rate before the first occurrence of relapse. The multivariate Cox proportional hazard method was utilized to identify risk factors associated with relapses of AOSD. Results: A total of 122 patients with AOSD were enrolled with a median follow-up of 12.6 months. Among them, 26 (21.3%) patients had at least one relapse. The cumulative relapse rates of AOSD patients were 14.42%, 21.79%, 24.81% and 28.57% at 6, 12, 18 and 36 months, respectively. According to the multivariate analysis, intensive treatment (odds ratio: 6.848; 95% CI: 2.441, 19.211) and macrophage activation syndrome (odds ratio: 4.020, 95% CI: 1.564, 10.322) were associated with increased risk of relapse. Conclusion: Our study indicated that relapses occurred in at least one-fifth of patients with AOSD, and patients with high disease severity at initial attack may have an increased risk of relapse, which needs more intensive therapy and close follow-up.